2014
DOI: 10.7603/s40933-014-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Student-Teacher Relationship and Student Academic Motivation

Abstract: This qualitative study investigates the link between student-teacher relationship and student's academic motivation. Two 16-year old male students from a public boarding school in the Peninsular of Malaysia were chosen as participants. Data were gathered from two unstructured interviews. Five themes within the student-teacher relationship were identified throughout the interviews: care, support, trust, approachable and expectation. The findings suggest that academic motivation is fostered when teachers show ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…The study also indicated that sportsmanship has no significant relationship with trust. This contrasts with the concept of sportsmanship, which refers to an individual's avoidance of potentially tense behavior, complaints, escalating difficulties, and a disrespectful attitude (Jasmi & Hin, 2014). It means that students' trust in lecturers, the students will not exhibit good sportsmanship behavior by taking a positive attitude.…”
Section: Resultsmentioning
confidence: 96%
“…The study also indicated that sportsmanship has no significant relationship with trust. This contrasts with the concept of sportsmanship, which refers to an individual's avoidance of potentially tense behavior, complaints, escalating difficulties, and a disrespectful attitude (Jasmi & Hin, 2014). It means that students' trust in lecturers, the students will not exhibit good sportsmanship behavior by taking a positive attitude.…”
Section: Resultsmentioning
confidence: 96%
“…Ayres et al (2004) ascribed teachers' success to several factors, the first of which are their relationships with their students. Likewise, Jasmi and Hin (2014), who examined the potential link between teacher-student rapport and student motivation, found that teacher support and teacher approachability was key to supporting this relationship. Within IEPs, where many students begin their programs of study immediately after high school, the teacher-student relationship looms large in the minds of both students who mandatorily spend a minimum of 18 contact hours in IEP classrooms every week (Reese & Helms, 2018;U.S.…”
Section: (14 Of 19) |mentioning
confidence: 99%
“…Furthermore, calculus teacher has shown compassion and cooperation to their students as well as appreciating students' point of view on the topics. In the study of Jasmi and Hin (2014), it is stated that an approachable teacher can build trust and care for students which is part of academic motivation. Note: a -Scale of 1 to 10, b -See Table 1 for details.…”
Section: Descriptive Statisticsmentioning
confidence: 99%